163 Relative Bioavailability of Bis-glycinate Bound Copper in Beef Steers Fed a High Antagonist Growing Diet. (7th May 2021) - Deters, Erin L; VanDerWal, Allison; VanValin, Katherine; Hansen, Stephanie L
Abstract: To assess relative bioavailability of an organic Cu source, 90 Angus-cross steers (265 ± 21 kg) were blocked by body weight to pens with GrowSafe bunks and randomly assigned to dietary Cu treatments (14–18 steers/treatment): 0 mg Cu/kg dry matter (DM; CON), 5 or 10 mg Cu/kg DM as Cu sulfate (CS5; CS10) or chelated bis-glycinate Cu (GLY5; GLY10). Steers were fed a common high antagonist growing diet (0.48% S; 5.3 mg Mo/kg DM; 4.9 mg Cu/kg DM). Blood was collected from all steers on d 0, 28, 56, 84 and 124. Liver samples were collected at trial beginning (d -3/-2) and end (d 125/126). Data were analyzed using ProcMixed of SAS (experimental unit = steer; fixed effect = treatment; random effect = block). Plasma Cu was analyzed as repeated measures (repeated effect = day). Plasma and liver Cu concentrations were regressed against Cu intake using ProcGLM to calculate relative bioavailability of GLY. Initial liver Cu did not differ between treatments (P ≥ 0.63), but final liver Cu was lesser in CON versus steers supplemented 5 or 10 mg Cu/kg DM from either source (P ≤ 0.09). Final liver Cu was greater for CS versus GLY (P < 0.01). Plasma Cu for all treatments decreased through d 28; final plasma Cu was greatest for steers supplemented either source at 10 mg Cu/kg DM (treatment × day P < 0.01). Relative bioavailability of GLY was 82% compared to CS (P < 0.01) based on liver Cu but did not differ based on plasma Cu (P = 0.60). High concentrations of dietary antagonists and lower solubility of GLY (68.9% relative to CS) in rumen-like conditions (pH 5.2) may have resulted in free thiomolybdate absorption across the rumen wall and subsequent depletion of liver Cu stores in GLY supplemented steers.